2021
DOI: 10.5114/amsad.2021.107817
|View full text |Cite
|
Sign up to set email alerts
|

Update on prevention of diabetic foot ulcer

Abstract: The diabetic foot ulcer is the most important reason for non-traumatic limb amputation. Based on recent data, it has been estimated that up to 34% of type 2 diabetes patients may develop diabetic foot ulcers once in their lifetime. Risk factors for developing foot ulcers are distal sensorimotor peripheral neuropathy, peripheral arterial disease, previous ulcers, and/or amputations. Understanding the factors that place patients with diabetes mellitus at high ulceration risk and the early treatment of risk facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 79 publications
0
12
0
1
Order By: Relevance
“…Neuropathy and PAD often co-exist and may lead to neuroischemic ulceration, and symptoms may be absent, despite severe peripheral ischemia. The combination of two or more of the above risk factors commonly results in ulceration [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Neuropathy and PAD often co-exist and may lead to neuroischemic ulceration, and symptoms may be absent, despite severe peripheral ischemia. The combination of two or more of the above risk factors commonly results in ulceration [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although this research has a significant contribution to knowledge, there are some limitations to this research. Diabetic foot ulcers can be detected in various ways, including checking blood glucose, HbA1c (Miranda, Da Ros, and Marfella 2021), ankle brachial index (ABI) (Yang et al 2021), monofilament examination (Baldursdottir et al 2020), TcPO2 . examination (Fagher and Löndahl 2021) as well as regular foot checks.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers mainly focus on medical treatment rather than prevention. Cesare Miranda[ 179 ] suggested that comprehensive management should be implemented to prevent DFUs and provided a flow chart for the prevention of DFUs, including DFU education, blood glucose control, management of PAD, identification of risky feet, regular inspection of susceptible feet, long-term wearing of appropriate shoes, and treatment of ulcer risk factors. DFU education can reduce the incidence of DFUs and amputations.…”
Section: Preventionmentioning
confidence: 99%